O tema do orçamento impositivo no ordenamento jurídico brasileiro - GODOY, ARNALDO SAMPAIO DE MORAES (Revista da AJURIS, 2014)
O artigo apresenta o tema do orçamento impositivo no ordenamento jurídico brasileiro. Defende-se que propostas legislativas de criação de um orçamento impositivo no contexto do direito financeiro brasileiro ofenderia a fórmula de freios e contrapesos, de independência e de harmonia entre os poderes constituídos, tal como se lê no art. 2º da Constituição brasileira. ABSTRACT: The paper faces the subject of the mandatory budget within the Brazilian legal framework. It argues that legislative proposals with the goal of creating a mandatory budget in the context of Brazilian financial law would offend the formula of checks and balances, threatening the harmony among the Government branches, as provided in the article 2 of the Brazilian constitution.